Analisis Keterampilan Membaca Puisi Dalam Materi Pembelajaran Bahasa Indonesia Pada Siswa Kelas VIII - Yulianingrum, Dystiani; Ulya Nurul Laili; Andi Wapa (JURNAL ILMU PENDIDIKAN, 2025)
The practice of poetry reading skills of eighth grade students based on aspects of pauses, pronunciation, intonation and expression and factors that influence poetry reading skills in students. This study aims to determine how the results of poetry reading skills practice in eighth grade students and factors that influence students' poetry reading skills. The research method used in this study is descriptive qualitative. Data collection techniques used are observation, tests, interviews, documentation, and online data searches. The practice of reading poetry students got the highest score in the pause aspect with an average score of 77.3 and the lowest average score in the expression aspect, namely 36 because students lack understanding in the expression aspect. This is influenced by several factors, namely internal factors and external factors through the results of a questionnaire given to 25 students containing 10 statements, especially in terms of self-confidence, understanding the meaning of poetry, interest, and environmental support shown by a high percentage of "inappropriate" answers to several important statements, such as self-confidence when performing in front of the class (60%), the habit of practicing at home (44%), understanding the meaning of poetry (48%), and low school environmental support (56%). Overall, improvements are needed in students' internal aspects (interest, motivation, and reading habits) and external aspects (support from teachers, friends, and the school environment) to support optimal poetry reading skills.